Metode Pelatihan di Sanggar Swargaloka dalam Mengembangkan Prestasi Siswa - Mutiarasari, Kartika (Program Studi Pendidikan Tari FBS UNJ, 2021)
This study aims to describe the existence of the Swargaloka dance studio as a studio capable of producing good and reliable dance artists, both dancers and choreographers, who often become champions in participating in dance competitions both at the local and national levels. Research is more focused on the implementation of training, namely on curriculum, instructors and training methods used. This research uses a qualitative approach. The data were collected through observation, interviews with group leaders, studio managers, instructors, students and parents of the Swargaloka / Swargaloka School of Dance studio students, observation, and active participation. The data obtained were in the form of oral and written data and recordings. Data were analyzed using the flow model because between activities concluding data, reducing, presenting in the form of conclusions were carried out in an interactive way. The results of this study are expected to be able to describe the implementation of training at Sanggar Swargaloka with the training methods, so as to produce students who have good achievements as dancers and choreographers. Until now, Swargaloka studio is always an example for studios in East Jakarta.